Echocardiography in the emergency department. Issue 2 (22nd January 2009) - Wright, J; Jarman, R; Connolly, J; Dissmann, P
Abstract : Point-of-care echocardiography using portable machines is an exciting development in emergency medicine. Recent improvements in ultrasound quality mean that emergency physicians are finding echocardiography useful in a variety of clinical settings. Evidence suggests that emergency physicians are able to master the skills of basic echocardiography sufficiently to improve patient care in the resuscitation scenario. Patients with clinical conditions such as breathlessness, undifferentiated shock, chest pain and cardiac arrest may benefit. There is a steep learning curve involved in acquiring these skills and the specialty needs to take care in the way that its practitioners are accredited and perform echocardiography.